KEDUDUKAN DEWAN PENGAWAS KPK DITINJAU DARI STRUKTUR KETATANEGARAAN REPUBLIK INDONESIA - Mayang Abrilianti (2021)
This study discusses the position of the KPK Supervisory Board in terms of the State Administration Structure of the Republic of Indonesia. Based on Law Number 19 of 2019, the KPK Supervisory Board was held after nearly 20 years of running this anti-corruption agency. In order to achieve more optimal public services for the community, the government considers it necessary to establish a KPK Supervisory Board. As an adjustment measure to the development of the Indonesian military structure even though its name is not listed in the 1945 Constitution of the Republic of Indonesia. There are many pros and cons of the existence of the KPK Supervisory Board which is considered to be able to hinder and even weaken the performance of the KPK itself. It seemed that it was suddenly completed in just a matter of months, and many things were covered regarding the consideration of the formation of this latest KPK Law, causing various kinds of polemics. The approach used in this research is normative juridical. By going through a statutory approach and a conceptual approach to explore deeper and answer the problems that exist in it. This research is a descriptive analysis that describes and concludes the problem is the object of research. The number of speculatives from several parties regarding the position of the KPK Supervisory Board from the constitutional structure, it can be concluded that based on the Constitutional Court Decision No.20 / PUU-XV / 2017 it is emphasized that the KPK is part of the executive as well as the supervisory organ, namely the KPK Supervisory Board, but it is underlined that both, including the Supervisory Board, must maintain high independence in terms of carrying out their duties and functions. The Supervisory Board was held with the consideration of abuse of power, legal violations of the KPK leadership to violations of the code of ethics within the KPK. So that the Supervisory Board is expected to be able to control the performance of the KPK as well as a check and balance instrument on the agreement of the President of the Republic of Indonesia and the DPR.